Modeling & Study of Micro structural Evolution of IN 718. (2020) - Janardhana, V.; Bikash, M.; Pradeep, J.K.; Sidharth, J.; Rahul, M.; Rao, A.
Abstract: Super alloy IN 718 is used in jet engine application, due to its creep properties and the structural stability at high temperatures. The mechanical properties are affected by the grain size. Control of grain size is the key issue that governs the mechanical properties. The dynamic recrystallization & grain size of IN 718 Cylindrical billet of 10 x 70 mm during Equal channel angular pressing (ECAP) is simulated and analyzed. Cellular Automata (CA) & Mehl-Johnson-Avrami models are used to predict recrystallization and grain growth behaviour, considering the two distinct regimes of dynamic and static recrystallization. Metal forming code DEFORM 3D has been used for numerical modelling that establishes the thermo mechanical history. The material parameters were found using thermo mechanical simulator Gleeble 3800 and also were collected from literature. The experimental results of ECAP processing the IN 718, at 1050 °C, Die & punch is kept at 450 °C, to avoid die chilling, is correlated to the simulated results. The initial average grain size is taken as 28 µm for CA & Avrami models. The IN 718 sample average initial grain size is 29 µm at room temperature.(The average Avrami grain size of IN 718 at 1050 °C, is 56 µm as per numerical simulations) The final Average grain size after ECAP process simulation is 23.3 µm & 22.9 µm by CA & Avrami models respectively. The experimental (after ECAP) average grain size obtained is 22.8 µm. The grains that are less than 10 µm are increased from 12 % initially to 40 % after ECAP.